All Days 2012
DOI: 10.2118/157055-ms
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Associated Surfactant Micellar Fluids: An Alternative to Crosslinked Polymer Systems

Abstract: Hydraulic fracturing has become an increasingly important completion method to allow reservoirs to become economically producible and to improve the rate of hydrocarbon production. Crosslinked polymer fluids have been the most commonly used fracturing fluid. These fluids exhibit exceptional performance to initiate and propagate a fracture and carry proppant into the reservoir during a treatment. However, crosslinked polymer fluids can leave a significant amount of polymer in the fracture once a treatment is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Nanoparticles are proposed as a novel alternative to enhance polymer gel properties. In the past few years, nanotechnology has been widely studied in the oil and gas industry [18][19][20][21][22][23][24]. Nanoparticles are particles that present a high surface area to volume ratio and a diameter size between 1 nm and 100 nm [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles are proposed as a novel alternative to enhance polymer gel properties. In the past few years, nanotechnology has been widely studied in the oil and gas industry [18][19][20][21][22][23][24]. Nanoparticles are particles that present a high surface area to volume ratio and a diameter size between 1 nm and 100 nm [19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the regular occurrence of thick filter cake and formation damage issues is overwhelming. When filter cake is not totally removed from fracture walls, fracture conductivity damage occurs (Crews et al, 2008;Crews and Gomaa, 2012). Adequate efforts should be geared towards preventing formation damage because the restoration of a damaged reservoir is difficult and costly (Krueger, 1986), especially in low permeability reservoirs like shale gas.…”
Section: Introductionmentioning
confidence: 99%
“…Increase low shear rate viscosity on Threadlike micelle fluids and more stable [36] Metal oxides based Improve fracturing fluid stability and viscosity at high temperature (300 F). [37] Non-ferrous NPS Combine with surfactant for IFT reduction [38] Refinery Nano-supported HDS Patent on nano-supported HDS catalyst [39] MoS 2 nano-catalyst Observe atomic-scale edge structures of MoS 2 [40] TiO 2 NPs Improve water treatment by reducing fouling effect [41] TiO 2 , ZrO 2 , and SiO 2 NPs…”
Section: Pyroelectric Npmentioning
confidence: 99%
“…Barati et al [74] applied polyelectrolyte complex NPs, which worked to clean up fracturing fluids by delaying the release of enzymes that cause premature gel breaking and improve fracturing efficiency. Crews and Gomaa [36] found that ZnO NPs could raise the low shear rate viscosity of threadlike micellar fluids that exhibit similar behavior as crosslinked polymer systems. Li et al [37] conducted experimental studies on the effect of metal oxide NPs on fracturing fluids and found that adding NPs to the fracturing fluid improved the viscosity by 23-116% at an elevated temperature and reduced polymer loading.…”
Section: Stimulation Process Improvementmentioning
confidence: 99%